Glycosylation Defects and Virulence Phenotypes of Leishmania mexicana Phosphomannomutase and Dolicholphosphate-Mannose Synthase Gene Deletion Mutants - Garami, Attila (American Society for Microbiology, 2001)
Leishmania parasites synthesize an abundance of mannose (Man)-containing glycoconjugates thought to be essential for virulence to the mammalian host and for viability. These glycoconjugates include lipophosphoglycan (LPG), proteophosphoglycans (PPGs), glycosylphosphatidylinositol (GPI)-anchored proteins, glycoinositolphospholipids (GIPLs), and N-glycans. A prerequisite for their biosynthesis is an ample supply of the Man donors GDP-Man and dolicholphosphate-Man. We have cloned from Leishmania mexicana the gene encoding the enzyme phosphomannomutase (PMM) and the previously described dolicholphosphate-Man synthase gene (DPMS) that are involved in Man activation. Surprisingly, gene deletion experiments resulted in viable parasite lines lacking the respective open reading frames (ΔPMM and ΔDPMS), a result against expectation and in contrast to the lethal phenotype observed in gene deletion experiments with fungi. L. mexicana ΔDPMS exhibits a selective defect in LPG, protein GPI anchor, and GIPL biosynthesis, but despite the absence of these structures, which have been implicated in parasite virulence and viability, the mutant remains infectious to macrophages and mice. By contrast, L. mexicana ΔPMM are largely devoid of all known Man-containing glycoconjugates and are unable to establish an infection in mouse macrophages or the living animal. Our results define Man activation leading to GDP-Man as a virulence pathway in Leishmania.